2000
DOI: 10.1007/s004019900173
|View full text |Cite
|
Sign up to set email alerts
|

Nonoxidative protein glycation is implicated in familial amyotrophic lateral sclerosis with superoxide dismutase-1 mutation

Abstract: To assess a role for oxidative stress in the pathogenesis of amyotrophic lateral sclerosis (ALS), we analyzed the immunohistochemical localization of 8-hydroxy2'-deoxyguanosine (OHdG) as a nucleic acid oxidation product, acrolein-protein adduct and 4-hydroxy-2-nonenal (HNE)-protein adduct as lipid peroxidation products, Nepsiloncarboxymethyl-lysine (CML) as a lipid peroxidation or protein glycoxidation product, pentosidine as a protein glycoxidation product, and imidazolone and pyrraline as nonoxidative protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 61 publications
2
39
0
Order By: Relevance
“…138,139 Furthermore, in familial ALS patients with A4V mutation, the concentration of 8-hydroxy-29 -deoxyguanosine (OHdG), the oxidation product of DNA via hydroxylation at the C-8 position, is not elevated but rather decreased in the motor cortex, 140 and no signi cant OHdG immunoreactivity is detected in the anterior horn cells. 141 These ndings form a striking contrast to evidence that sporadic ALS patients show elevated OHdG concentration in the motor cortex and spinal cord 140,142 and intense OHdG immunoreactivity in the anterior horn cells. 140,141 Therapeutic trials with an antioxidant N-acetyl cysteine do not result in prolonged survival of G93A transgenic mice or sporadic ALS patients.…”
Section: Increased Oxidative Damagementioning
confidence: 64%
“…138,139 Furthermore, in familial ALS patients with A4V mutation, the concentration of 8-hydroxy-29 -deoxyguanosine (OHdG), the oxidation product of DNA via hydroxylation at the C-8 position, is not elevated but rather decreased in the motor cortex, 140 and no signi cant OHdG immunoreactivity is detected in the anterior horn cells. 141 These ndings form a striking contrast to evidence that sporadic ALS patients show elevated OHdG concentration in the motor cortex and spinal cord 140,142 and intense OHdG immunoreactivity in the anterior horn cells. 140,141 Therapeutic trials with an antioxidant N-acetyl cysteine do not result in prolonged survival of G93A transgenic mice or sporadic ALS patients.…”
Section: Increased Oxidative Damagementioning
confidence: 64%
“…Analyzing SALS spinal cords, it was found immunoreactivity to HNE-histidine and crotonaldehyde-lysine, indicative of lipid peroxidation; carboxymethyl-lysine (CML), indicative of lipid peroxidation or protein glycoxidation; and pentosidine, indicative of protein glycoxidation [120]. In an other study it was also found that the pattern of immunoreactivity in FALS spinal cord was quite different, with intense immunoreactivity for CML bit also for pyrraline, marker of non oxidative protein glication, and in the Lewy body-like inclusion only and imidazolone -another marker of non oxidative protein glication -immunoreactivity in the cytoplasm of the residual motor neurons [121].…”
Section: Amyotrophic Lateral Sclerosismentioning
confidence: 89%
“…A recent study (54) demonstrated that LTB 4 12HD was effective at reducing a wide variety of cytotoxic ␣,␤-unsaturated aldehydes and ketones including products of lipid peroxidation such as 4-hydroxy-2-nonenal (HNE). HNE has been shown to be elevated in the cerebrospinal fluid of SALS cases (55) and SALS spinal cord (56,57). A potential chemoprotective role for the enzyme was suggested by its ability to confer resistance of LTB 4 12HD-transfected cell lines to HNE-induced apoptosis (54).…”
Section: Discussionmentioning
confidence: 99%